Abstracts - 1989 Colloquium Amherst, Nova Scotia: Atlantic Geoscience Society

(untitled) (Atlantic Geoscience Society, 1989)
The 1989 Colloquium of the Atlantic Geoscience Society was held at the Wandlyn Inn, Amherst, Nova Scotia on February 3-4, 1989. On behalf of the Society we thank Laing Ferguson of Mount Allison University and all others involved in the organization of the meeting. In the following pages we publish the abstracts of talks and poster sessions given at the meeting.